Perfomance of Broiler Chickens Given Drinking Water Contains Young Coconut Water, Palm Sugar, or Molasses - I M. D. A., Susila; Siti, N. W.; Udayana, I D. G. A. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the performance of broiler chickens given drinking water containing young coconut water, palm sugar, and molasses. The research was carried out on privately owned farms in Batannyuh Village, Regency Tabanan which lasted for 5 weeks. One hundred broilers were used with body weight of 116 ± 3.17 grams. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. Each replication consists of 5 chickens. The four treatments are A: drinking water without electrolytes as control, B: drinking water plus 1% young coconut water, C: drinking water plus 1% palm sugar, and D: drinking water plus 1% molasses. The variables observed in this study were initial body weight, final weight, feed consumption, drinking water consumption, weight gain, Feed Conversion Ratio (FCR), and  Income Over Feed and Chick Cost (IOFCC). The results showed that treatment C had a final body weight, weight gain and efficiency of ration use significantly lower (P <0.05) than treatment B, but not significantly (P> 0.05) lower than treatments A and D. The results of the research also showed that treatment B had a final body weight, weight gain, and efficiency of using rendum tends to be higher (P> 0.05) than treatments A and D. Based on the results of the study it was concluded that broiler chickens whose drinking water was given additional water Young coconut gives a better tendency than other treatments, especially for broiler chickens whose drinking water is given palm sugar gives the best performance on final body weight, weight gain, and efficient use of rations, and so also regarding the economic aspects.